Cognitive Level Analysis of Problems in Mathematics Textbook Class XII Revision 2018 Materials of Congress and Construction Based on the Revised Bloom Taxonomy - Dira Oktia Mita; Ringki Agustinsa; Edi Susanto (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
Abstract:This study aims to describe the distribution of cognitive levels of questions in the 2018 Revised Class XII Mathematics Textbook for Congruence and Similarity Based on Bloom's Taxonomy. Bloom's Taxonomy used is a revised Bloom's Taxonomy with cognitive process dimensions consisting of: remembering(C1), understanding(C2), applying(C3), analyzing(C4), evaluating(C5), and creating(C6). This type of research was descriptive research with a qualitative approach. Sources of data in this study were questions about the material congruence, similarity and competency test questions contained in the mathematics textbooks of class XII students. The research was carried out with the method of collecting documentation data and using research instruments in the form of analysis sheets and analysis conformity sheets. The results showed that the distribution of the cognitive level of questions on the congruence and similarity material contained the cognitive level of understanding(C2) as much as 18.2%, applying(C3) as much as 50% and analyzing(C4) as much as 31.8%, with the dominant cognitive level being cognitive level of applying(C3) and does not include cognitive levels of remembering(C1), evaluating(C2) and creating(C6). So it was found that the distribution of the cognitive level of the questions on the material of congruence and similarity topic did not vary or was not proportional. with the dominant cognitive level being cognitive level of applying(C3) and does not include cognitive levels of remembering(C1), evaluating(C2) and creating(C6). So it was found that the distribution of the cognitive level of the questions on the material of congruence and similarity topic did not vary or was not proportional. with the dominant cognitive level being cognitive level of applying(C3) and does not include cognitive levels of remembering(C1), evaluating(C2) and creating(C6). So it was found that the distribution of the cognitive level of the questions on the material of congruence and similarity topic did not vary or was not proportional. Keywords: Mathematics Textbook, Congruence, Similarity, Question, Revised Bloom's Taxonomy, Cognitive Level.